García-Huidobro, Joaquín, Comunidad : la palabra que falta, Valencia, Tirant Humanidades, 2020, 285 pp - Menem, Paulina (2022)
Fil: Menem, Paulina. Pontificia Universidad Católica Argentina; Argentina